Microstructure and wear properties of plasma-sprayed aluminum-silicon-polyester coatings - Öksüz, M; Yildirim, H; Erturan, S (WILEY, 2006)
Powder coatings, which are made, by plasmaspraying processes, are being used in industrial applications because of their wear resistance, chemical resistance, and high impact strength even at low service temperatures. These factors increase the importance of plastic and plastic-based coatings in industrial applications. In this study, an aluminum-silicon-polyester-based composite coating was applied by plasmaspraying processes with and without an intermediate bond coat (Ni-Al). The effects of the coating thickness, intermediate bond coat, and processes parameters on the microstructure and wear properties of the coating were studied experimentally. The wear properties of the coatings were determined according to ball-on-disk procedure. The microstructures of the coating were examined by optical microscopy and scanning electron microscopy. The results indicated that the plasma-spraying current and thickness had a strong influence on the wear resistance and rnicrostructural properties of the aluminum-silicon-polyester coating. (c) 2006 Wiley Periodicals, Inc.
Keywords: coatings; morphology; structure-property relations; BEHAVIOR; Polymer Science